Circulación y conexión mundial de saberes - Antonio Arellano Hernández; Rigas Arvanitis; Dominique Vinck (Revue d'anthropologie des connaissances)
The authors show how scientific and technological research in Latin America has become institutionalised and has given rise to science policy questions and debates. This development has become a subject of study. Thus, the text describes the emergence and development of social studies on science in Latin America since the 1950s with the development of an original Latin American thought on science and technology (PLACTS), the formation of the first social studies on science and technology (STS) research groups working on scientific disciplines and producing diagnoses on the scientific development, then the institutionalisation of these STS studies and the consolidation of research groups in this domain giving rise to new approaches concerning the conditions of scientific development in a peripheral context, the social and local utility of scientific and technological knowledge, the processes of re-signifying established knowledge, the creation of new relations between research and industry and the emergence of research policies. Finally, the text shows how Latin American researchers are today questioning the articulations between local and globalized knowledge, between local activities and policies and global networks, and the role of technological knowledge in Latin America in a globalized world, which raises a reflexive questioning of the role of STS-produced research in Latin American societies.